Enhancing Customer E-Loyalty and E-WOM: The Role of Electronic and Non-Electronic Service Quality and Customer Satisfaction (PLN Mobile Application) - Aji Lesmana; Tengku Ezni Balqiah (Petra International Journal of Business Studies, 2023)
This study examines the relationships between six constructs: e-service quality, customer e-satisfaction service quality, customer satisfaction, customer e-loyalty, and electronic word-of-mouth (EWOM). The study collected data from 452 respondents who are customers of PLN and have used the PLN Mobile application. The study found that customer e-loyalty can be directly and indirectly influenced by service and e-service quality. Both customer satisfaction and e-satisfaction can mediate the influence of service quality and e-service quality on customer e-loyalty. Therefore, PLN needs to ensure service quality (both through the application and field personnel) and customer satisfaction with the services provided to enhance customer satisfaction and foster electronic loyalty, encouraging customers to continue using the PLN Mobile application. The study also reveals that customer e-loyalty positively and significantly influences EWOM.